Ecological Perspectives in Language Learning: Mapping theoretical diversity for pedagogical transformations - Aisyiyah, Siti; Novawan, Adriadi; Ismailia, Titik (P3M Politeknik Negeri Jember, 2026)
Ecological perspectives represent a paradigm shift in language learning, moving from reductionist models to frameworks that embrace complexity, relationality, and context-embeddedness. This state-of-the-art paper examines five major ecological approaches: affordance-centered (Gibson, van Lier), systems-based (Bronfenbrenner, CHAT), complexity/dynamic systems theory (Larsen-Freeman), critical ecological (ecolinguistics), and holistic/situated perspectives, and their classroom adoption through affordance-based pedagogy, multi-system interventions, and ecopedagogy. Six paradigm shifts mark their influence: from input to affordance, individual to relational, linear to dynamic, decontextualized to embedded, transmission to transformation, and technology as tool to ecological mediator. These shifts have profound implications for pedagogy, research, teacher education, and policy, empowering teachers to make informed, context-appropriate decisions while foregrounding questions of morality, equity, and justice. As digital transformation and climate crisis reshape educational landscapes, ecological perspectives offer essential conceptual tools for creating language education that is more effective, equitable, and empowering.